Review article. Usnic acid: potential alternative against current bacterial resistance - Avila-Zamora, Sharon Juliet (2023)
Usnic acid (AU) is a lichen substance, which is part of the secondary metabolites of lichens, which are organisms that generate a symbiosis between a photosynthetic organism and a mycobiont, such as Usnea sp, produced by different metabolic pathways, such as this is the case of the AU substance resulting from the acetate-malonate pathway. On the other hand, the extraction of UA is carried out by means of organic solvents, maceration and for its identification, high efficiency liquid chromatography (HPCL) is carried out. Lichen substances have antimycotic, antiviral, cytotoxic, and antimicrobial characteristics, the latter has been studied against pathogenic bacteria such as Staphylococcus sp., Escherichia coli, Streptoccocus sp., among others, due to antiquity of hospital prevalence, due to the fact that they have developed resistance against used antibiotics, concern; Therefore, new alternatives are being sought that allow us to continue fighting these pathogens. The mechanisms of action used by UA have been investigated, among which are the ability to inhibit the synthesis of bacterial primers, preventing their replication. has confirmed its in vitro use against multiresistant bacteria such as Staphylococcus aureus MRSA, showing that UA has a minimum inhibitory concentration (MIC) of 25–50 μg/mL [1]. The UA inhibition mechanism can lead to bacterial growth arrest; through mechanisms such as replication inhibition (DNA-RNA) in addition to the inhibition of bacterial resistance genes, thus shielding this possible antibiotic against resistant bacterial strains currently found.